A novel approach of encapsulating curcumin and succinylated derivative in mannosylated-chitosan nanoparticles. (1st December 2022) - Idoudi, Sourour; Hijji, Yousef; Bedhiafi, Takwa; Korashy, Hesham M.; Uddin, Shahab; Merhi, Maysaloun; Dermime, Said; Billa, Nashiru
Abstract: Curcumin (CUR) manifests anti-colon cancer activity but suffers from low solubility, bioavailability, and instability, rendering it not as effective as its chemotherapeutic cousins. Here, we conjugate CUR to succinic anhydride (SA), (CUR.SA conjugate), subsequently formulated in mannose-conjugated chitosan nanoparticles (CUR-NPs and CUR.SA-NPs). Instrumental analyses confirmed formation of CUR.SA and mannosylated chitosan (CM) conjugates, with CUR.SA being less crystalline thus, more soluble. Average particle size of CUR-NPs and CUR.SA-NPs were 268 ± 6 nm and 342 ± 4.6 nm, with drug entrapment of 93.34 ± 0.40 % and 98.46 ± 0.06 % respectively. In vitro releases of CUR and CUR.SA from nanoparticles in pH 1.2 and 6.8 media were slow and sustained over 2 h and 72 h, respectively. The physical characteristics of the nanoparticles were unchanged over 3 weeks of storage. Thus, a successful CUR.SA conjugate has been developed, couriered in CM nanoparticles, with favorable attributes that warrant further anti-colon cancer studies, which is ongoing. Graphical abstract: Unlabelled Image